1989
DOI: 10.1177/0013161x89025002003
|View full text |Cite
|
Sign up to set email alerts
|

Expertise in Principals' Problem Solving

Abstract: To identify the central elements in school principals 'problem-solving processes and the differences between "experts" and their more typical colleagues, 22 elementary principals were interviewed. We analyzed their responses to brief hypothetical case problems and proposeda model of problem-solving components. Differences between expert and typical principals were most evident in response to "messy" or ill-structured problems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
75
0

Year Published

1990
1990
2014
2014

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 103 publications
(80 citation statements)
references
References 17 publications
5
75
0
Order By: Relevance
“…The findings from this study are consistent with results from two other studies: one by Leithwood and Stager (1989) concerning principals' problem-solving strategies and the other by Campbell-Evans (1988) which investigated the influence of values on principals' decision making using Beck's (1984aBeck's ( , 1984b value model. Leithwood and Stager found that principles or values served to provide structure for problem solving when principals lacked problem-relevant information or when the problem was considered unique.…”
Section: Discussionsupporting
confidence: 90%
“…The findings from this study are consistent with results from two other studies: one by Leithwood and Stager (1989) concerning principals' problem-solving strategies and the other by Campbell-Evans (1988) which investigated the influence of values on principals' decision making using Beck's (1984aBeck's ( , 1984b value model. Leithwood and Stager found that principles or values served to provide structure for problem solving when principals lacked problem-relevant information or when the problem was considered unique.…”
Section: Discussionsupporting
confidence: 90%
“…Leithwood and Jantzi (2000) and Leithwood and Steinbach (1995) emphasize that these transformational leadership behaviors consist of problem-solving processes to further promote organizational change and improvement.…”
Section: Transformational Leadershipmentioning
confidence: 99%
“…This was likely the case for staff trying to decide whether and how to implement a "house system," since they had had no previous related experience. These problems had significant elements that might be labelled "unstructured," as defined in our previous research (see Leithwood and Stager, 1989). Principals did not have a significant amount of problem-relevant knowledge on which to draw, and their goals were ill defined.…”
Section: Resultsmentioning
confidence: 99%
“…This classification system includes four major categories of values and some 16 specific values within these categories, as outlined later in table 2. Leithwood and Stager (1989) used the six categories in the model to describe differences between the problem-solving processes of expert and typical elementary school principals working individually. Leithwood and Steinbach(in press)also used the model to describe the problem solving of chief education officers (Ontario's directors of education).…”
Section: A Model Of Administrative Problem Solvingmentioning
confidence: 99%